KONSEP DIRI WANITA MENOPAUSE DI DESA LEDUG KECAMATAN KEMBARAN KABUPATEN BANYUMAS - Desiyani Nani; Anti Mugianti (Kesmas Indonesia, 2009)
Menopause is natural phase in every women’s life who is signed with the ended of menstruation cycle. In Indonesia, menopause is ussualy happen at 45 to 55ages. Menopause women gets threaten towards self system, which can be danger to social integrity function, identity, and self esteem (self concept) so that itcan be influencing to activity in their life interpersonally both in home and working area. The objective of this research was to prove the difference of self concept of working menopause woman and non – working menopause women at Ledug village of Kembaran sub district of Bnyumas region. This research was quantitative research with cross sectional of study approach, means that variables that were examined in this research were collected on the same time. Population in this research was women who were 45 to 55 yearsold with number of 585 women at Ledug village of Kembaran sub district of Banyumas region. The technique of taking sample used purposive sampling. The sample was47 working menopause women and 47 non- working menopause women. Data analyst method that was used was chi square test. Based on the result of research showedself concept of working menopause women concept with number of 4 women (36,4%) while self concept of non – working menopause women that were categorized as positive with number of 40 women (48,2) and negative self concept were 7 women (63,6). The result of chi squere experiment were got analysis result p = 0,336 (p>a = 0,005) means there was no significant difference of self concept of working menopause women and non – working menopause women at Ledug village of Kembaran sub district of Banyumas region. There was no significant difference of self concept of working menopause women and non – working menopause women at Ledug village of kembaran sub district of Banyumas region.